Change agency and urban vulnerability: Theological-ecclesial paralysis or deep solidarity - Beer, Stephan de (HTS teologiese studies, 2021)
Globally, cities respond differently to their most vulnerable urban populations, notably so during the coronavirus disease 2019 (COVID-19) pandemic. In the City of Tshwane, there seems to be a general paralysis of the church and theological education in relation to urban vulnerability. If the church and theological education are to participate as change agents to help transform urban vulnerability, a deliberate theological praxis and deep urban diaconate – in solidarity with the city’s most vulnerable realities – are proposed. This is done with reference to Harvey Cox’s assertion that the task of the church in the city is that of Diakonos and the provocations of Philippino liberation theologian, Daniel Pilario.Contribution: This article proposes that urban vulnerability and various responses to it need to be reflected upon as a priority, much more deliberately, considering how the entire urban household (oikos) is at risk.